Review paper A reappraisal of concepts in heart failure: Central role of cardiac power reserve - Williams, Simon G.; Barker, Diane; Goldspink, David F.; Tan, Lip-Bun (Archives of Medical Science, 2005)
Of all cardiological conditions, heart failure (HF) is by far conceptually the most difficult to grasp. For over a century, it has been beset with a number of misconceptions, which require reappraisal. Central to these misleading concepts is the absence of a reliable means of evaluating what constitutes heart failure and how to assess and ameliorate its severity. To attain this necessitates our moving away from the easier assessments at rest to measurements at peak exercise. Taking the key function of the cardiac pump as the delivery of adequate hydraulic energy to maintain the requisite circulation, it becomes apparent that the parameter we require is cardiac power output reserve, which incorporates both the flow- and pressure-generating capacity of the heart. Evidence available so far has shown that this variable is a major determinant of exercise incapacity and prognosis in patients with heart failure.